Inhabited Machines Genealogy of an Architectural Concept - Gleich, Moritz (Exploring Architecture, 2022)
Around 1800, one of the most influential architectural concepts of the last 250 years emerged-that of built spaces as technical devices. Climate, morality, and comfort are the three main themes of this study, and each is vividly examined through synchronous comparison and with the help of examples. The book is aimed at readers interested in architecture, technology or the cultural history of building and living.